Decoding behaviour and connectivity mental system in second language context: critical period and the lateralization of language function - Figueiredo, Sandra (2018)
The factors that distinguish individuals in the second language (L2) acquisition process are age, gender, the neuronal and cognitive maturation, previous linguistic knowledge and the psychological and affective aspects. The environment influence must not be understood as another isolated factor, but as the determinant background that implies all the factors considered. The aim of our general research project, on the basis of two empirical studies, is to present the process of L2 acquisition in a holistic style, considering the cognitive and affective perspectives. The research that has been developed in the language acquisition area disclosed some results, which allow perceiving that several psychological, biological, and neuropsychological factors are involved actively in the predisposition of the individual with migratory experience for his/her psychosocial and academic growth. Method: Regarding the lack subsisting in the second language acquisition research, it was developed a assessment instrument to observe the different verbal behaviour of 130 students (7-30 years old), with monolingual and second language learning profiles, at several cognitive and linguistic levels, considering age, gender and also all the migratory experience profiles. Results and Conclusions: Findings in what concerns the decoding competence will be discussed, regarding phonological awareness, memory, auditory and visual discrimination. The results of the dichotic hearing test (in the second language learners sample) will be here discussed, applying to the critical period of discriminating behaviour. We suggest a hypothesis of a mental linguistic system of connectivity (of functions) that could be stabilized/fossilized in the younger learners, that, in addition to the abilities of abstractness yet not full developed, result in a linguistic achievement decrease.